Diminished activity-dependent BDNF signaling differentially causes autism-like behavioral deficits in male and female mice - Ma, Kaijie; Taylor, Connie; Williamson, Mark; Newton, Samuel S.; Qin, Luye (Frontiers in Psychiatry, 2023)
Autism spectrum disorder (ASD) is a group of neurodevelopmental disorders with strong genetic heterogeneity and more prevalent in males than females. Recent human genetic studies have identified multiple high-risk genes for ASD, which produce similar phenotypes, indicating that diverse genetic factors converge to common molecular pathways. We and others have hypothesized that activity-dependent neural signaling is a convergent molecular pathway dysregulated in ASD. However, the causal link between diminished activity-dependent neural signaling and ASD remains unclear. Brain-derived neurotrophic factor (BDNF) is a key molecule mediating activity-dependent neural signaling. We therefore hypothesize that diminished activity-dependent BDNF signaling could confer autism-like behavioral deficits. Here, we investigated the effect of diminished activity-dependent BDNF signaling on autism-like behavioral deficits by using mice with genetic knock-in of a human BDNF methionine (Met) allele, which has decreased activity-dependent BDNF release without altering basal BDNF level. Compared with wild-type (WT) controls, diminished activity-dependent BDNF signaling similarly induced anxiety-like behaviors in male and female mice. Notably, diminished activity-dependent BDNF signaling differentially resulted in autism-like social deficits and increased self-grooming in male and female mice, and male mice were more severe than female mice. Again, sexually dimorphic spatial memory deficits were observed in female BDNF+/Met mice, but not in male BDNF+/Met mice. Our study not only reveals a causal link between diminished activity-dependent BDNF signaling and ASD-like behavioral deficits, but also identifies previously underappreciated sex-specific effect of diminished activity-dependent BDNF signaling in ASD. These mice with genetic knock-in of the human BDNF Met variant provide a distinct mouse model for studying the cellular and molecular mechanisms underlying diminished activity-dependent neural signaling, the common molecular pathway dysregulated in ASD.